1999
DOI: 10.1017/s1355838299982134
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of tRNA nuclear export with processing of tRNA

Abstract: Eukaryotic tRNAs are synthesized in the nucleus and need to be exported to the cytoplasm where they function in translation. tRNA export is mediated by exportin-t, which binds tRNA directly and with high affinity. tRNAs are initially synthesized as precursor molecules. Maturation to functional tRNA takes place in the nucleus, precedes export, and includes trimming of the 59 and 39 ends, posttranscriptional addition of the 39 CCA end, nucleoside modifications, and in some cases splicing. Here we address the que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
162
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(173 citation statements)
references
References 42 publications
8
162
1
Order By: Relevance
“…Studies of the binding capability of vertebrate exportin-t and crystallography studies of S. pombe Los1 in complex with tRNA and Ran-GTP showed that this exportin preferentially interacts with the appropriately structured tRNA backbone (the D and TcC loops of the L-shaped tertiary structure) as well as the mature tRNA 59 and 39 ends (Arts et al 1998b;Lipowsky et al 1999;Cook et al 2009;Lee et al 2011). Moreover, in vivo studies in S. cerevisiae demonstrated that tRNAs with altered sequence accumulate in the nucleus (Qiu et al 2000).…”
Section: Los1mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the binding capability of vertebrate exportin-t and crystallography studies of S. pombe Los1 in complex with tRNA and Ran-GTP showed that this exportin preferentially interacts with the appropriately structured tRNA backbone (the D and TcC loops of the L-shaped tertiary structure) as well as the mature tRNA 59 and 39 ends (Arts et al 1998b;Lipowsky et al 1999;Cook et al 2009;Lee et al 2011). Moreover, in vivo studies in S. cerevisiae demonstrated that tRNAs with altered sequence accumulate in the nucleus (Qiu et al 2000).…”
Section: Los1mentioning
confidence: 99%
“…Although exportin-t/Los1 monitors the tRNA backbone and aminoacyl stem, it does not monitor the anticodon stem as vertebrate exportin-t binds intron-containing and spliced tRNAs with equal affinity (Arts et al 1998b;Lipowsky et al 1999). In yeast, Los1's in vivo interaction with introncontaining pre-tRNAs is evidenced by the fact that splicing in yeast occurs only after nuclear export on the outer surface of mitochondria and los1D cells accumulate intron-containing tRNA in the nucleus (Sarkar and Hopper 1998;Yoshihisa et al 2003Yoshihisa et al , 2007.…”
Section: Los1mentioning
confidence: 99%
“…In this case, newly synthesized aminoacyl-tRNA synthetases would enter the nucleus, either as free enzymes that assemble into a multienzyme complex or as a preformed complex. Synthetases would then associate with their cognate tRNAs, and multiple tRNAs and synthetases would be transported to the cytoplasm together, perhaps in cooperation with exportin-t (21,22) or EF1 (32). One advantage of such a model would be to maintain a cytoplasmic ratio of tRNA to cognate synthetase of 1:1 and would result in partial assembly of the cytoplasmic translation apparatus already in the nucleus.…”
Section: Figmentioning
confidence: 99%
“…Exclusion of defective tRNA from the cytoplasm was shown to be due to nuclear proofreading, and it was proposed that aminoacylation of tRNA serves as this proofreading step (18 -20). While there is still some discussion whether aminoacylation or binding to the nuclear export receptor, exportin-t, is actually responsible for proofreading, there is agreement that nuclear aminoacylation increases tRNA export efficiency (21,22).…”
mentioning
confidence: 99%
“…The role of Los1 in tRNA export is conserved in many, but not all, organisms. Xpo-t, the Los1 vertebrate homolog, efficiently binds end-processed, intron-containing pre-tRNA and mature tRNA (Arts et al 1998b;Lipowsky et al 1999;Cook et al 2009). Orthologs of Los1 in plants (PAUSED) (Hunter et al 2003) and vertebrates (Xpo-t) (Arts et al 1998a;Kutay et al 1998) participate in tRNA nuclear export.…”
Section: Introductionmentioning
confidence: 99%